2015
DOI: 10.1242/bio.011825
|View full text |Cite
|
Sign up to set email alerts
|

Matrix compliance and the regulation of cytokinesis

Abstract: Integrin-mediated cell adhesion to the ECM regulates many physiological processes in part by controlling cell proliferation. It is well established that many normal cells require integrin-mediated adhesion to enter S phase of the cell cycle. Recent evidence indicates that integrins also regulate cytokinesis. Mechanical properties of the ECM can dictate entry into S phase; however, it is not known whether they also can affect the successful completion of cell division. To address this issue, we modulated substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…In their model, the fibroblasts in tumors show altered cell-matrix adhesion, increased migration, and changed mechanics, which might stimulate cancer cells to migrate toward stromal regions that are less dense, and thereby increase the size of a tumor. Moreover, cell-matrix stiffness has been shown to stimulate cytokinesis, which suggests that the increased stiffness of the surrounding fibroblasts can also stimulate the proliferation of cancer cells (37). These ideas are in line with our findings that these RhoA-KO tumor-promoting fibroblasts showed increased homogeneous stiffness and fewer soft locations, with altered cytoskeleton and cell-matrix adhesion.…”
Section: Discussionsupporting
confidence: 89%
“…In their model, the fibroblasts in tumors show altered cell-matrix adhesion, increased migration, and changed mechanics, which might stimulate cancer cells to migrate toward stromal regions that are less dense, and thereby increase the size of a tumor. Moreover, cell-matrix stiffness has been shown to stimulate cytokinesis, which suggests that the increased stiffness of the surrounding fibroblasts can also stimulate the proliferation of cancer cells (37). These ideas are in line with our findings that these RhoA-KO tumor-promoting fibroblasts showed increased homogeneous stiffness and fewer soft locations, with altered cytoskeleton and cell-matrix adhesion.…”
Section: Discussionsupporting
confidence: 89%
“…[22][23][24]26 To investigate the fate of binucleated cells induced by loss of substrate adhesion, human fibroblast MRC-5 mitotic cells were isolated by mitotic shake off, maintained in suspension for 30 min to allow mitotic progression, seeded in growth medium and analyzed for several parameters at different time points. Parallel cultures were treated with the microtubule inhibitor nocodazole (NOC) for 3 hrs, then released in drug-free medium for 30 min to allow reformation of the mitotic spindle and subjected to the same procedure ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Concordantly, inhibition of intercellular bridge abscission and fusion of connected daughter cells have been demonstrated by live cell imaging of dermal fibroblasts performing cytokinesis on experimentally generated soft substrates. 26 Binucleated cells produced by cytokinesis in suspension preferentially arrest in the G2 phase…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that the compliance of the adhesion substrate impacts integrin signaling and cytokinesis (23,24). Our studies with SIMS cells were performed on culture plates, whose stiffness is orders of magnitude higher than observed in tissues (25).…”
Section: Discussionmentioning
confidence: 99%
“…Much of what is known about the mechanisms that regulate cytokinesis in mammalian cells has been acquired from experiments in culture using cell lines that are easily transfected and imaged (22). However, since integrin signaling can be strongly influenced by substrate compliance (23), and our previous studies demonstrated that cytokinesis is regulated by matrix compliance in a cell typedependent manner (24), it is important to demonstrate that pathways that regulate cytokinesis in cell culture similarly regulate cytokinesis in a more physiological complex context. Since we previously demonstrated that α6 integrins promote successful cytokinesis in embryonic salivary glands in ex vivo organ culture (14), we again used this model to test whether RSK2 regulates cytokinesis and MKLP1 expression in this context.…”
Section: Rsk2 Regulates the Expression Of Mklp1 In The Embryonic Salimentioning
confidence: 99%